Дослідження руху насіння в аспіраційному каналі пневмогравітаційного сепаратора методами числових експериментів - Колодій, Олександр Сергійович; Колодий, Александр Сергеевич; Kolodii, Oleksandr; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Kiurchеv, Serhii; Мельник, К. Л. (СНАУ, 2016)
UK: У даній статті приведені результати руху насіння в аспіраційному каналі пневмогравітаційного сепаратора методами числових експериментів. Представлені результати числового трифакторного експерименту показують раціональні параметри: швидкість вводу насінин в потік повітря, кут вводу, та максимальне розщеплення траєкторії насіння соняшника. RU: В данной статье приведены результаты движения семян в аспирационном канале пневмогравитацийного сепаратора методами численных экспериментов. Представлены результаты численного трифакторного эксперимента показывают рациональные параметры: скорость ввода семян в поток воздуха, угол ввода, и максимальное расщепление траектории семян подсолнечника.EN: In this article the urgency to develop new tools and new methods of separation of sunflower seeds. The analysis of previous studies of famous scientists in the separation of oilseeds proved that scientists have made a significant contribution to the process of separation of seeds, but in our opinion the process of separation of sunflower seeds in the vertical aspiration channel with lower discharge was given insufficient attention, so you should develop and explore pnevmohravitatsiynyy separator with bottom unloading sunflower seeds. By Reviewed motion seeds in the aspiration channel separator pnevmohravitatsiynoho methods of numerical experiments. The results of numerical experiments show tryfaktornoho rational parameters developed pnevmohravitatsiynoho separator speed input seeds in airflow angle input and maximum splitting trajectory sunflower seeds.
Исследование движения семян в аспирационном канале пневмогравитацийного сепаратора методами численных экспериментов
Investigation of the seeds in the aspiration channel separator pnevmohravitatsiynoho methods of numerical experiments
Keywords: сепарація; аспіраційний канал; пневмогравітаційний сепаратор; насіння соняшника; сепарация; аспирационный канал; пневмогравитацийний сепаратор; семена подсолнечника; separation; aspiration channel pnevmohravitatsiynyy separator; sunflower seeds